THE EVOLUTIONARY TRENDS AND GEOGRAPHIC DISTRIBUTION OF THE TETHYAN MARKER PALEOCENE BENTHIC FORAMINIFERAL SPECIES OF ANAN - Haidar Salim Anan (Science Heritage Journal)
Twenty-four diagnostic Paleocene benthic foraminiferal species of Anan, which related to eighteen genera were erected from five widely separated countries in the Southern and Northern Tethys, its proposed evolutionary trends of them, and the taxonomic revision of these taxa, which will greatly aid paleontologists and biostratigraphers to helpfully understanding. Thirteen species of them were erected from Egypt ((Siphogaudryina strougoi, Pseudoclavulina hewaidyi, P. youssefi, Annulofrondicularia bignoti, Tristix aubertae, Lenticuzonaria misrensis, Percultazonaria alii, P. ameeri, Palmula berggreni, P. salimi, Vaginulinopsis boukharyi, Citharina plummerae, Gyroidinoides luterbacheri), five species from UAE (Repmanina mazeni, Psammolingulina bahri, Laevidentalina hudae, Hemirobulina olae, Ramulina futyani), three species from Pakistan (Textularia haquei, Spiroloculina haquei, S. pakistanica), two species from Jordan: (Pseudoclavulina futyani, Lenticuzonaria hodae), and one species of them is recorded from Tunisia (Leroyia tunisica). The paleogeographic distribution of these taxa are recorded in some other countries in the Southern and Northern Tethys than the original type locality, e.g. Iran, Czech, Bulgaria and Argentina. Some of these species are used to introduce an evolutionary trend marked by changes in the morphology and other characters of these benthic foraminiferal test. The Southern Tethys assemblage indicates an open marine environment, which represents middle-outer neritic environment and shows an affinity with Midway-Type Fauna (MTF).